Penerapan Sistem Akuntansi Penjualan Tiket Pada Pt. ASDP Indonesia Ferry Cabang Sorong - Naila, Safira; Kahina, Dwi Iin; Masseni (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2025)
This research was conducted at PT. ASDP Indonesia Ferry Sorong Branch, which still uses a manual system for its sales system. The purpose of this research is to find out how the ship ticket sales accounting system is running at PT. ASDP Indonesia Ferry Sorong Branch. The analysis technique used in this research is qualitative descriptive analysis. And data collection uses interview, observation and documentation techniques. Sales system at PT. ASDP Indonesia Ferry Sorong Branch has cash payments, payments can be made in cash or via online bank transfer for boat ticket sales. To purchase tickets, the manual method is still used, namely service users must purchase tickets at the ticket sales counter at the PT office. ASDP Indonesia Ferry Sorong Branch. Information regarding ship departure schedules can be accessed via PT social media. ASDP Indonesia Ferry Sorong Branch.